How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15387632 ZenodoArchiveConcept: 15387631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1117 2405685:SB7G3I83
Keywords: _r:AddedByMyEducationEvidence

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15692961 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1123 ZenodoArchiveConcept: 15692960
Keywords: _r:AddedByMyEducationEvidence

Artificial Intelligence in Education Across Bangladesh: Findings from a rapid scan and key informant interviews - Honda, Delanie; Ahmed, Shakil; Ramesh Vasudevan, Sharanya (EdTech Hub, 2025)
This Helpdesk Report was developed in response to a request from the UK's Foreign Commonwealth and Development Office (FCDO) Bangladesh for a rapid scan on the use of Artificial Intelligence (AI) in Bangladesh’s education system. The report aims to provide education decision-makers with accessible, evidence-based summaries of best practices in specific areas of EdTech, in this case, the AI landscape in Bangladesh. Using a combination of desk research and key informant interviews, the scan provides insights for the FCDO by highlighting key actors, early use cases, opportunities, and challenges, and to support future thinking about AI’s role in education, particularly as Bangladesh is preparing for its next development education plan — the Primary Education Sub-Sector Programme. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 16573142 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1133 ZenodoArchiveConcept: 16573141
Keywords: _r:AddedByMyEducationEvidence

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15851578 ZenodoArchiveConcept: 15851577 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7782171 10.53832/edtechhub.0160 10.53832/edtechhub.1129 2405685:333BJPIR
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen